2018
DOI: 10.1002/ajim.22828
|View full text |Cite
|
Sign up to set email alerts
|

Pleural abnormalities and exposure to elongate mineral particles in Minnesota iron ore (taconite) workers

Abstract: There was evidence of a mild to moderate increase in pleural abnormalities in this population of miners, associated with geographically non-specific cumulative EMP exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Since then, Perlman et al. ( 2018 ) reported that chest x‐rays of spouses of taconite workers have not shown pleural or parenchymal abnormalities above background. This finding provides supporting evidence of a lack of exposure to EMPs for community members who were not themselves occupationally exposed to asbestos.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, Perlman et al. ( 2018 ) reported that chest x‐rays of spouses of taconite workers have not shown pleural or parenchymal abnormalities above background. This finding provides supporting evidence of a lack of exposure to EMPs for community members who were not themselves occupationally exposed to asbestos.…”
Section: Discussionmentioning
confidence: 99%
“…The existing epidemiological and toxicological data do not support increased risk of cancers from nonasbestiform amphibole EMPs in Northshore workers (Allen et al., 2014 , 2015a , 2015b ; Lambert et al., 2016 ). Although cumulative EMP exposure was associated with the prevalence of pleural abnormalities in taconite workers on the MIR, the association was not specific to workers potentially exposed to nonasbestiform amphibole EMPs and the prevalence of pleural abnormalities was not elevated in the spouses of workers (Perlman et al., 2018 ). The results of particulate matter characterization from independent sampling of ambient air in the MIR communities is consistent with the Silver Bay ambient air monitoring data (Monson Geerts et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%